Ratio Legis Perbedaan Rumusan Delik Pasal 2 dan Pasal 3 Undang-Undang Nomor 31 Tahun 1999 Jo. Undang-Undang No. 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi - Gatot Triyanto (Fakultas Hukum Universitas Islam Jember, 2017)
The qualification of criminal acts of corruption is as stated in Article 2 and Article 3 of Law no. 31 year 1999 jo. UU no. Law No. 20 of 2001. In further detail, according to Article 2, the meaning of a criminal act of corruption has the following elements: Every person; Unlawfully; Perform an enriching act of self or another person or a corporation; Which can harm the state finance or state economy. Whereas according to Article 3 the elements of corruption acts, are as follows: Every person; For the purpose of benefiting oneself or others or a corporation; Abuses any authority, opportunity or means available to him due to position or position, which may harm the state's finances or the economy of the country. Article 2 and Article 3 mentioned above, there are differences and similarities. The equality of the two chapters lies in the imposition of the